Ex vivo biotransformation of lady’s mantle extracts via the human gut microbiota: the formation of phenolic metabolites and their impact on human normal and colon cancer cell lines - Jakimiuk, Katarzyna; Kruk, Aleksandra; Lemieszek, Marta Kinga; Strawa, Jakub W.; Granica, Sebastian; Wiater, Adrian; Tomczyk, Michał (Frontiers in Pharmacology, 2025)
IntroductionFor centuries, various species from the genus Alchemilla have been utilized in traditional medicine worldwide. Among them, Alchemilla vulgaris L. (Rosaceae) stands out as a promising herbal drug candidate due to its phytochemicals displaying anti-inflammatory and antioxidant properties.MethodsIn our study, we investigated the interaction between the human gut microbiota and lady’s mantle herb extract (AV) following the biotransformation of the extract’s constituents and their impact on colorectal cancer cells (HT-29) and normal CCD 841 CoN epithelial cells. The A. vulgaris herb metabolites were obtained by incubating the extract (AV) with human fecal slurries from three healthy donors (D1, D2, and D3).ResultsAfter incubating the AV extract with the human gut microbiota (AVD1-AVD3 samples), thirty-three metabolites were detected and characterized by LC-MS. Among them, one was identified as urolithin C. The AV and AVD1-AVD3 extracts and their metabolites exhibit various levels of antiproliferative and cytotoxic activities against cancer cells. Their biological effect might be linked to the changes and direct activity of bioavailable metabolites. Samples from AVD1, AVD2, and AVD3 increase the lactate dehydrogenase (LDH) released from damaged colon cancer cells in a dose-dependent manner. At 250 μg/mL, AVD1, AVD2, and AVD3 elevated the LDH level by 12.6%, 25.3%, and 30.0%, respectively. The biotransformed samples also showed significantly higher antiproliferative activity than the AV extract. The most active sample from donor 3 (AVD3) reached IC50 = 471 μg/mL.DiscussionThe differences in anticancer effect might be linked to the changes and direct activity of bioavailable metabolites. The non-transformed AV extract affected neither normal nor cancer colon cells, indicating the beneficial effect of the biotransformation procedure on the anticancer properties of the evaluated extracts. The above results clearly indicate that microbial metabolism is a crucial factor that is potent in altering the biological activity of lady’s mantle extract.